Perovskite layer with passivated surface and method for improving photoelectric conversion efficiency of perovskite solar cell

By designing a terminal functionalized organic potassium salt, 4-hydroxyphenyl trifluoroborate, which is dissolved in a low-polar solvent, to modify the perovskite layer interface, the problem of poor solubility of existing passivating agents in low-polar solvents is solved, and the photoelectric conversion efficiency and stability of perovskite solar cells are significantly improved.

CN119836123APending Publication Date: 2025-04-15SHENZHEN POLYTECHNIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411981083.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The solubility of the passivator used in low-polar solvents in existing perovskite solar cells is poor, which limits its effectiveness in practical applications and leads to insufficient charge transfer efficiency and stability.

Method used

Design and develop an end-group functionalized organic potassium salt, 4-hydroxyphenyltrifluoroborate, which is soluble in low-polar solvents such as isopropanol, for modifying the interface of the perovskite layer. The structural integrity of the material is enhanced by synchronous passivation of anion defects and cation defects through various methods such as Lewis acid-base coordination and hydrogen bonding.

Benefits of technology

It effectively improves the surface defects and charge transport performance of perovskite films, improves the photoelectric conversion efficiency and stability of solar cells, simplifies the preparation process and improves the application flexibility of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836123A_ABST
    Figure CN119836123A_ABST
Patent Text Reader

Abstract

The invention provides a surface-passivated perovskite layer and a method for improving the photoelectric conversion efficiency of a perovskite solar cell. The surface-passivated perovskite layer comprises a perovskite active layer and a surface passivation layer attached to the surface of the perovskite active layer, and the surface passivation layer is obtained by attaching a dispersion liquid of 4-hydroxyphenyl potassium trifluoroborate to the surface of the perovskite active layer. By forming the surface passivation layer, the photoelectric conversion efficiency of the prepared perovskite solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photovoltaic power generation, and in particular relates to a surface passivated perovskite layer and a method for improving the photoelectric conversion efficiency of a perovskite solar cell. Background Art

[0002] In the research field of perovskite solar cells, interface engineering is considered to be one of the key factors to improve cell performance. In recent years, carbon-based perovskite solar cells have attracted widespread attention due to their superior conductivity and low cost. However, the interfacial properties on the surface of the perovskite layer often affect the charge transfer efficiency and stability. At present, a variety of interface modification methods have been proposed, including the use of polymers, inorganic materials and other organic molecules. Although these methods have improved the interfacial compatibility to a certain extent, there are still problems such as solubility, stability and insufficient conductivity. Especially in low-polarity solvents, many traditional modifiers such as passivators represented by potassium salts have poor solubility, which limits their effectiveness in practical applications.

[0003] Therefore, designing and developing an organic potassium salt that can be well dissolved in low-polarity solvents for modifying the perovskite interface will provide a new solution for improving the overall performance of carbon-based perovskite solar cells. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art to at least some extent. The present invention aims to directionally design an end-group functionalized organic potassium salt so that it can be dissolved in a low-polarity solvent such as isopropanol, so as to effectively modify the upper interface of the perovskite film of the carbon-based perovskite solar cell. By improving the surface defects and charge transfer performance of the perovskite film, the photoelectric conversion efficiency and stability of the battery are improved. At the same time, by utilizing the characteristics of low-polarity solvents, the preparation process can be simplified, the application flexibility of the material can be improved, and the application range of potassium salt passivators in perovskite devices can be expanded. This innovation is expected to provide important technical support for the commercialization of carbon-based perovskite solar cells.

[0005] Specifically, the present invention provides the following technical solutions:

[0006] A first aspect of the present invention provides a surface passivated perovskite layer, comprising a perovskite active layer and a surface passivation layer attached to the surface of the perovskite active layer.

[0007] The surface passivation layer is obtained by attaching a dispersion of 4-hydroxyphenyl potassium trifluoroborate on the surface of the perovskite active layer.

[0008] During the research process, it was found that 4-hydroxyphenyl potassium trifluoroborate (K[BF3-Ph-OH]), as an organic potassium salt, has a terminal alcohol hydroxyl group that can be dissolved in low-polarity solvents (such as isopropanol). It has a Lewis-basic trifluoroborate and a Lewis-acidic potassium ion, which can simultaneously passivate anion defects and cation defects through Lewis acid-base coordination, hydrogen bonding and other methods. At the same time, the π-π interaction of the main benzene ring provides a possibility for reducing the energy level of the defect. In addition, potassium ions can fill the cation missing sites in the perovskite structure, especially the A-site defects (such as the lack of lead or methylamine ions), and enhance the structural integrity of the material. After the perovskite film is post-treated with 4-hydroxyphenyl potassium trifluoroborate, the surface defects are effectively passivated to form a surface passivation layer. The surface roughness of the treated film is significantly reduced, the crystallinity and energy level matching are significantly improved, and the carrier transport capacity is effectively enhanced. The surface defect state density of the perovskite film after K[BF3-Ph-OH] treatment is reduced, and the photoelectric performance and environmental stability are further improved, thereby improving the photoelectric conversion efficiency of perovskite solar cells.

[0009] According to an embodiment of the present invention, the dispersion of potassium 4-hydroxyphenyl trifluoroborate is a dispersion obtained by dissolving potassium 4-hydroxyphenyl trifluoroborate in a non-polar solvent.

[0010] According to an embodiment of the present invention, the non-polar solvent is at least one of isopropanol, ethyl acetate and chlorobenzene.

[0011] According to an embodiment of the present invention, the dispersion of potassium 4-hydroxyphenyl trifluoroborate is an isopropanol dispersion of potassium 4-hydroxyphenyl trifluoroborate, and the mass concentration of the isopropanol dispersion of potassium 4-hydroxyphenyl trifluoroborate is 0.5 mg / mL to 1.5 mg / mL.

[0012] According to an embodiment of the present invention, the method is as follows:

[0013] Performing a first annealing on a precursor solution including a perovskite active material to form a perovskite active layer;

[0014] At a rotation speed of 4000-6000 rpm, an isopropanol dispersion of 4-hydroxyphenyl potassium trifluoroborate is spin-coated on the surface of the perovskite active layer, and the surface-passivated perovskite layer is obtained through a second annealing.

[0015] According to an embodiment of the present invention, the first annealing temperature is 100-120° C., and the annealing time is 40-100 minutes;

[0016] The second annealing temperature is 100-120°C.

[0017] A second aspect of the present invention provides a perovskite solar cell, comprising:

[0018] Basal layer,

[0019] An electron transport layer, wherein the electron transport layer is disposed on the surface of the substrate layer;

[0020] A surface-passivated perovskite layer, wherein the surface-passivated perovskite layer is the surface-passivated perovskite layer described in the first aspect;

[0021] A hole transport layer, the hole transport layer being disposed on the surface of the surface-passivated perovskite layer;

[0022] A counter electrode layer is located on the surface of the hole transport layer.

[0023] According to an embodiment of the present invention, the substrate layer is selected from at least one of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass;

[0024] The material of the electron transport layer is selected from at least one of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3;

[0025] The material of the hole transport layer is selected from at least one of Spiro-OMe TAD, PEDOT:PSS, P3HT, nickel oxide, vanadium oxide, and phthalocyanine materials;

[0026] The material of the counter electrode layer is carbon.

[0027] A third aspect of the present invention provides a method for improving the photoelectric conversion efficiency of a perovskite solar cell, comprising:

[0028] A surface passivation layer is attached to the surface of the perovskite active layer of the perovskite solar cell,

[0029] The surface passivation layer is obtained by attaching a dispersion of 4-hydroxyphenyl potassium trifluoroborate on the surface of the perovskite active layer and performing annealing.

[0030] According to an embodiment of the present invention, the dispersion of 4-hydroxyphenyl potassium trifluoroborate is an isopropanol solution of 4-hydroxyphenyl potassium trifluoroborate.

[0031] The beneficial effects achieved by the present invention are at least:

[0032] 1) The organic potassium salt designed and used in the present invention is used to modify the surface of perovskite, which has a simple process and low cost.

[0033] 2) The organic potassium salt surface passivation molecule used in the present invention has a hydroxyl end group that ensures its solubility in the isopropanol solvent, and can utilize the aromatic benzene ring to construct a hydrophobic perovskite protective layer while effectively passivating various surface defects. The short-circuit current density and fill factor of the passivated photovoltaic device are significantly improved, and the device has higher photoelectric conversion efficiency and humidity stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The figure is a flow chart of post-processing of a perovskite solar cell according to the present invention.

[0035] Figure 2 This is a scanning electron microscope (SEM) image of a perovskite film provided according to an embodiment of the present invention.

[0036] Figure 3 This is a comparison chart of the photoelectric conversion efficiency between the experimental group and the control group provided according to an embodiment of the present invention. DETAILED DESCRIPTION

[0037] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0038] A first aspect of the present invention provides a surface passivated perovskite layer, comprising a perovskite active layer and a surface passivation layer attached to the surface of the perovskite active layer.

[0039] The surface passivation layer is obtained by attaching a dispersion of 4-hydroxyphenyl potassium trifluoroborate on the surface of the perovskite active layer.

[0040] After surface passivation with K[BF3-Ph-OH], the crystallinity of perovskite can be effectively enhanced, the energy level matching can be improved, and the humidity stability of the perovskite layer can be increased, so as to realize the preparation of efficient and stable carbon-based perovskite photovoltaic devices. It can be applied to solar cells, light-emitting diodes, photoelectric emission and photodetectors.

[0041] The perovskite active layer materials of perovskite solar cells are mainly composed of organic-inorganic hybrid metal halides with an ABX3 structure, where A is an organic or inorganic monovalent cation (such as formamidine, methylamine, cesium ion, etc.), B is a divalent metal ion (such as lead, tin, etc.), and X is a halogen (such as chlorine, bromine, iodine, etc.) or a mixture thereof. Common perovskite active layer materials include formamidine lead iodine (FA 0.85 MA 0.15PbI3), methylamine lead iodide (CH3NH3PbI3), cesium lead iodide (CsPbI3), etc. These materials have excellent photoelectric properties such as high absorption coefficient, high carrier mobility, and low exciton binding energy. According to a specific embodiment, the chemical formula of the perovskite active layer mentioned is (FAPbI3) 0.98 (MAPbBr3) 0.02 , which can be deposited and effectively grown on the surface of the electron transport layer. There are many methods for preparing the perovskite active layer, including but not limited to solution coating, vapor deposition, etc.

[0042] According to a specific embodiment, the dispersion of potassium 4-hydroxyphenyl trifluoroborate is a dispersion obtained by dissolving potassium 4-hydroxyphenyl trifluoroborate in a non-polar solvent.

[0043] According to a specific embodiment, the non-polar solvent includes but is not limited to isopropanol, ethyl acetate, chlorobenzene, etc. According to a preferred embodiment, the non-polar solvent is isopropanol.

[0044] According to a specific embodiment, the dispersion of potassium 4-hydroxyphenyl trifluoroborate is an isopropanol dispersion of potassium 4-hydroxyphenyl trifluoroborate, and the mass concentration of the isopropanol dispersion of potassium 4-hydroxyphenyl trifluoroborate is 0.5 mg / mL to 1.5 mg / mL, for example, 0.8 to 1.0 mg / mL.

[0045] According to an embodiment of the present invention, the method is as follows:

[0046] Performing a first annealing on a precursor solution including a perovskite active material to form a perovskite active layer;

[0047] At a rotation speed of 4000-6000 rpm, an isopropanol dispersion of 4-hydroxyphenyl potassium trifluoroborate is spin-coated on the surface of the perovskite active layer, and the surface-passivated perovskite layer is obtained through a second annealing.

[0048] According to an embodiment of the present invention, the first annealing temperature is 100-120° C., and the annealing time is 40-100 minutes;

[0049] The second annealing temperature is 100-120°C.

[0050] The present invention also provides a perovskite solar cell, comprising:

[0051] Basal layer,

[0052] An electron transport layer, wherein the electron transport layer is disposed on the surface of the substrate layer;

[0053] A surface-passivated perovskite layer, wherein the surface-passivated perovskite layer is the surface-passivated perovskite layer described in the first aspect;

[0054] A hole transport layer, the hole transport layer being disposed on the surface of the surface-passivated perovskite layer;

[0055] A counter electrode layer is located on the surface of the hole transport layer.

[0056] According to an embodiment of the present invention, the substrate layer is selected from at least one of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass;

[0057] The material of the electron transport layer is selected from at least one of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; according to a preferred embodiment, the material of the electron transport layer is a dense TiO2 layer (c-TiO2) and a tin oxide layer (SnO2).

[0058] The material of the hole transport layer is selected from at least one of Spiro-OMe TAD, PEDOT:PSS, P3HT, nickel oxide, vanadium oxide, and phthalocyanine materials;

[0059] The material of the counter electrode layer is carbon.

[0060] The present invention also provides a method for improving the photoelectric conversion efficiency of a perovskite solar cell, comprising:

[0061] A surface passivation layer is attached to the surface of the perovskite active layer of the perovskite solar cell,

[0062] The surface passivation layer is obtained by attaching a dispersion of 4-hydroxyphenyl potassium trifluoroborate on the surface of the perovskite active layer and performing annealing.

[0063] According to an embodiment of the present invention, the dispersion of 4-hydroxyphenyl potassium trifluoroborate is an isopropanol solution of 4-hydroxyphenyl potassium trifluoroborate.

[0064] The technical scheme of the present invention is described below by specific examples. It should be noted that these examples are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention. Unless otherwise specified, the reagents used in the examples can be obtained commercially.

[0065] Example 1

[0066] Example 1 Reference Figure 1 As shown, a perovskite solar cell is prepared by the following method, comprising:

[0067] 1) Preparation of conductive FTO transparent substrate:

[0068] The etched FTO substrate was ultrasonically treated with distilled water, detergent, ethanol and isopropanol for 15 minutes in sequence, and then the isopropanol on the surface of the conductive substrate was removed with nitrogen gas, and finally dried.

[0069] 2) Preparation of electron transport layer:

[0070] The cleaned substrate (10 cm×10 cm) of step 1) was placed on a titanium hot plate, and the temperature was gradually increased to 450° C. The c-TiO2 solution was evenly sprayed on the substrate by spray pyrolysis and naturally cooled to room temperature.

[0071] After the deposition of c-TiO2 is completed, the substrate is cut into rectangular pieces of 1.67cm*2.5cm. The cut substrate is placed in a UV ozone cleaner for 15 minutes. Then the substrate is transferred to a spin coater and the SnO2 colloidal dispersion is statically spin-coated onto the substrate at 3000rpm for 30s. After the spin coating is completed, it is immediately placed on a 150℃ hot plate for 30 minutes. After annealing, it is naturally cooled to room temperature.

[0072] 3) Preparation of perovskite layer + surface passivation layer:

[0073] The substrate after SnO2 deposition in step 2) is treated with ultraviolet ozone and then subjected to a one-step spin coating method.

[0074] According to the chemical formula (FAPbI3) 0.98 (MAPbBr3) 0.02 The precursor was dissolved in a solvent of DMF:DMSO (4:1 by volume) and shaken for at least 15 minutes before use. 0.8 mg K[BF3-Ph-OH] was added to 1 mL of isopropanol (IPA) solution and stirred at room temperature for 4 h to obtain a post-treatment solution.

[0075] The first step is to spin-coat the precursor solution on the substrate in step 2) and anneal it; the spin-coating conditions are 1000 rpm for 10 seconds and then 5000 rpm for 30 seconds ((acceleration 2000 rpm / s 2 ), 100 μL EA was dropped in the last 15-20 seconds; annealing conditions were 100°C, 60 min; after the film was cooled to room temperature, post-treatment was carried out, and K[BF3-Ph-OH] IPA dispersion was dynamically spin-coated on the surface at 5000 rpm for 30 s, and a surface-passivated perovskite film was obtained after annealing at 100°C for 10 min (the control group did not undergo post-treatment).

[0076] 4) Preparation of hole transport layer:

[0077] The thin film prepared in step 3) is used to prepare a hole transport layer by a one-step spin coating method.

[0078] 10 mg of P3HT was dissolved in 1 mL of chlorobenzene and shaken to obtain a hole transport material solution A. Then, solution A was statically spin-coated onto the surface of the perovskite film obtained in step 3) at 3000 rpm for 30 s. After the spin coating was completed, it was immediately placed on a hot plate at 110 ° C for 5 min. After cooling, NiO with a concentration of 10 mg / mL was added. x / IPA dispersion B is spin-coated onto the surface of the above-mentioned hole material A, and finally a hole transport layer is obtained on the surface of the perovskite film after annealing at 65°C for 5 minutes.

[0079] 5) Preparation of the electrode layer:

[0080] Finally, the low-temperature carbon electrode was prepared by screen printing.

[0081] Figure 2 The following are scanning electron microscope (SEM) images of the perovskite films prepared in the experimental group and the control group of Example 1 of the present invention. The control group did not undergo the above-mentioned post-treatment process. Figure 2 It can be seen that the surface roughness of the perovskite film in the experimental group is reduced.

[0082] In addition, multiple indicators of the control group and the experimental group were tested. PCE test was obtained by combining the solar simulator and the digital source meter efficiency test system to test the device JV curve. Before the test, the standard silicon cell was used as a reference and the calibrated light intensity was 1 standard sunlight (AM1.5 G, 100mW / cm 2 ). PCE (photovoltaic conversion efficiency) refers to the efficiency of solar cells in converting received light energy into electrical energy, and is a key indicator for measuring battery performance. PCE is determined by Voc, Jsc and FF. Among them, Voc (open circuit voltage) refers to the voltage difference between the two ends of the solar cell when the external circuit is disconnected. Jsc (short circuit current density) refers to the current density under short circuit conditions. FF (fill factor) refers to the ratio of the maximum power point voltage (VMP) to the product of the open circuit voltage (Voc) and the maximum power point current (JMP). The results are shown in Table 1 below.

[0083] Control group Experimental Group <![CDATA[Jsc(mA / cm 2 )]]> 25.14 25.13 Voc(V) 0.94 0.97 FF(%) 64.41 66.43 PCE(%) 15.26 16.21

[0084] Figure 3 The comparison of the photoelectric conversion efficiency of the experimental group and the control group is shown in Table 1. Figure 3 It can be seen from the given results that the present invention improves the photoelectric conversion efficiency of perovskite solar cells.

[0085] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementation methods", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0086] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A surface passivated perovskite layer, characterized in that: It includes a perovskite active layer and a surface passivation layer attached to the surface of the perovskite active layer. The surface passivation layer is obtained by attaching a dispersion of 4-hydroxyphenyl potassium trifluoroborate on the surface of the perovskite active layer.

2. The surface-passivated perovskite layer according to claim 1, characterized in that The dispersion of potassium 4-hydroxyphenyl trifluoroborate is a dispersion obtained by dissolving potassium 4-hydroxyphenyl trifluoroborate in a non-polar solvent.

3. The surface-passivated perovskite layer according to claim 2, characterized in that: The non-polar solvent is at least one of isopropanol, ethyl acetate and chlorobenzene.

4. The surface-passivated perovskite layer according to claim 1, characterized in that The dispersion of potassium 4-hydroxyphenyl trifluoroborate is an isopropanol dispersion of potassium 4-hydroxyphenyl trifluoroborate, and the mass concentration of the isopropanol dispersion of potassium 4-hydroxyphenyl trifluoroborate is 0.5 mg / mL to 1.5 mg / mL.

5. The surface passivated perovskite layer according to claim 1, characterized in that Prepared by the following method: Performing a first annealing on a precursor solution including a perovskite active material to form a perovskite active layer; At a rotation speed of 4000-6000 rpm, an isopropanol dispersion of 4-hydroxyphenyl potassium trifluoroborate is spin-coated on the surface of the perovskite active layer, and the surface-passivated perovskite layer is obtained through a second annealing.

6. The surface-passivated perovskite layer according to claim 5, characterized in that The first annealing temperature is 100-120° C., and the annealing time is 40-100 minutes; The second annealing temperature is 100-120°C.

7. A perovskite solar cell, characterized in that: include: Basal layer, An electron transport layer, wherein the electron transport layer is disposed on the surface of the substrate layer; A surface-passivated perovskite layer, wherein the surface-passivated perovskite layer is the surface-passivated perovskite layer according to any one of claims 1 to 6; A hole transport layer, the hole transport layer being disposed on the surface of the surface-passivated perovskite layer; A counter electrode layer is located on the surface of the hole transport layer.

8. The perovskite solar cell according to claim 7, characterized in that: The substrate layer is selected from at least one of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass; The material of the electron transport layer is selected from at least one of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; The material of the hole transport layer is selected from at least one of Spiro-OMe TAD, PEDOT:PSS, P3HT, nickel oxide, vanadium oxide, and phthalocyanine materials; The material of the counter electrode layer is carbon.

9. A method for improving the photoelectric conversion efficiency of a perovskite solar cell, characterized in that: include: A surface passivation layer is attached to the surface of the perovskite active layer of the perovskite solar cell, The surface passivation layer is obtained by attaching a dispersion of 4-hydroxyphenyl potassium trifluoroborate on the surface of the perovskite active layer and performing annealing.

10. The method according to claim 9, characterized in that The dispersion of 4-hydroxyphenyl potassium trifluoroborate is an isopropanol solution of 4-hydroxyphenyl potassium trifluoroborate.